Effect of alkyl chain length and amylose/amylopectin ratio on the structure and digestibility of starch-alkylresorcinols inclusion complexes. (December 2022) - Fan, Haoran; Chen, Zhijun; Ma, Ruolan; Wen, Yangyang; Li, Hongyan; Wang, Jing; Sun, Baoguo
Abstract: Starch can form inclusion complexes with various phenolic compounds. The structure of phenolic compound and the amylose/amylopectin ratio of starch affect their complexing ability and functional properties. In this study, 5-heptadecylresorcinol (ARs-17) and 5-heneicosylresorcinol (ARs-21) were screened and the influences of amylose content on the formation and physicochemical properties of starch-alkylresorcinols (ARs) inclusion complexes were evaluated by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), nuclear magnetic resonance (NMR), and differential scanning calorimetry (DSC). The digestion curves and logarithm-of-slope (LOS) plots were obtained by in vitro digestion experiments. The results demonstrated that waxy maize starch (WMS) was not able to form inclusion complexes with ARs-17 or ARs-21, however, the possibility of ARs adsorption on amylopectin existed. For normal maize starch (MS), it could only form inclusion complex with ARs-21, and there was uncomplexed ARs in the inclusion complex due to its lower proportion of amylose. High amylose starches (G50 and G80) formed VII-type inclusion complexes with both ARs-17 and ARs-21, especially a small amount of VI-type inclusion complexes was present in ARs-21 inclusion complexes. Meanwhile, the crystallinity, thermal stability, and anti-digestive properties of starch-ARs inclusion complexes increased with the increment of ARs alkyl chain length and amylose content. This study suggested that high amylose starch facilitated stable delivery of ARs, which could improve the bioaccessibility of ARs. Graphical abstract: Image 1 Highlights: The higher content of amylose and longer alkyl chain length facilitated complexation. High amylose starch formed both VI and VII inclusion complexes with ARs-21. In case of insufficient amylose, ARs were likely to adsorb on amylopectin. The reduced digestion was due to the ordered structure or ARs inhibition on enzymes.